First person - Amanda Miles (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Amanda Miles is first author on ' Usher syndrome type 1-associated gene, pcdh15b, is required for photoreceptor structural integrity in zebrafish', published in DMM. Amanda is a PhD student in the lab of Vincent Tropepe at the University of Toronto, Toronto, Canada, investigating disease modelling for retinal development and disease mechanisms.